A SIMPLE APPROACH FOR UNDERSTANDING SEISMIC WAVE PROPAGATION IN POROUS MEDIA - Fakhriyadi Saptono; Suprajitno Munadi (Scientific Contributions Oil and Gas, 1999)
A simple approach for understanding seismic wave propagation in, porous media has been developed based on the effect of stress gradient on compressibility of the matrix and the fluid. The fluid saturation is accommodated in the bulk density formulation. The approach started from Gassmann theoretical formulation followed by simplifying the mathematical detail by substituting their physical aspects. Finally a practical formula for core analysis purposes is introduced. The theoretical concepts and experimental results appear to be in a good agreement.